Stress and Recurrent Miscarriage - Bhandari, S (Nepal Journal of Obstetrics and Gynaecology, 2012)
Stress has long been suspected as a possible cause of unexplained recurrent miscarriage. But while a relationship has been noted, we didn't know exactly how a woman's stress could cause miscarriage. Three “Super-systems”-the endocrine, immune, and nervous systems engage in multiple interactions during the body’s response to stress. Here we briefly discuss the possible mechanisms of stress induced changes on these systems leading to miscarriage. NJOG 2011 Nov-Dec; 6 (2): 2-6 DOI: http://dx.doi.org/10.3126/njog.v6i2.6747